Habitat, species richness and hantaviruses of sigmodontine rodents within the Interior Atlantic Forest, Paraguay. - Gillian Eastwood; Jeremy V Camp; Yong Kyu Chu; Aubrey M Sawyer; Robert D Owen; Xueyuan Cao; Mariah K Taylor; Leonardo Valdivieso-Torres; Richard D Sage; Ashley Yu; Doug G Goodin; Vicente J Martinez Bruyn; et al. (PLoS ONE, 2018)
Four of the nine sigmodontine tribes have species that serve as reservoirs of rodent-borne hantaviruses (RBO-HV), few have been studied in any depth. Several viruses have been associated with human cases of hantavirus pulmonary syndrome often through peridomestic exposure. Jabora (JABV) and Juquitiba (JUQV), harbored by Akodon montensis and Oligoryzomys nigripes, respectively, are endemic and sympatric in the Reserva Natural de Bosque Mbaracayú (RNBM), Paraguay, a protected area of the Interior Atlantic Forest. Rodent communities were surveyed along a 30 km stretch of the RNBM in eight vegetation classifications (Low, High, Bamboo, Riparian and Liana Forests, Bamboo Understory, Cerrado, and Meadow/Grasslands). We collected 417 rodents from which 11 species were identified; Akodon montensis was the predominant species (72%; 95%CI: 64.7%-76.3%), followed by Hylaeamys megacephalus (15% (11.2%-18.2%)) and Oligoryzomys nigripes (9% (6.6%-12.4%)). We examined the statistical associations among habitat (vegetation class) type, rodent species diversity, population structure (age, sex, and weight), and prevalence of RBO-HV antibody and/or viral RNA (Ab/RNA) or characteristic Leishmania tail lesions. Ab/RNA positive rodents were not observed in Cerrado and Low Forest. A. montensis had an overall Ab/RNA prevalence of 7.7% (4.9%-11.3%) and O. nigripes had an overall prevalence of 8.6% (1.8%-23.1%). For A. montensis, the odds of being Ab/RNA positive in High Forest was 3.73 times of the other habitats combined. There was no significant difference among age classes in the proportion of Ab/RNA positive rodents overall (p = 0.66), however, all 11 RNA-positive individuals were adult. Sex and habitat had independent prognostic value for hantaviral Ab/RNA in the study population; age, presence of tail scar/lesion (19% of the rodents) and weight did not. Adjusting for habitat, female rodents had less risk of becoming infected. Importantly, these data suggest habitat preferences of two sympatric rodent reservoirs for two endemic hantaviruses and the importance of including habitat in models of species diversity and habitat fragmentation.